Implementasi Nilai-Nilai Pancasila Dalam Proses Belajar Pada Sekolah Dasar Negeri Kincang 1 Jiwan (Eduscotech, 2023)
The values of Pancasila must be known, understood, and implemented by the Indonesian people in everyday life in order to realize the ideals of the proclamation of Indonesian independence. increasingly degraded and eroded by the invasion of new values that are not in accordance with national identity. This problem of understanding resulted in the abandonment and oblivion of Pancasila. Therefore, it is necessary to re-actualize the values of Pancasila so that they can be used as a reference for the Indonesian people in responding to various problems faced now and in the future, both problems that come from within and from outside. before our success in re-actualizing the values of Pancasila led to the alienation of Pancasila from the real life of the Indonesian nation.